Copper-aluminum catalyst, preparation method, application and regeneration method of copper-aluminum catalyst
By preparing the oxide copper-aluminum catalyst of Cu, Al and additive metals, the problem of poor activity and stability of copper-based catalysts is solved, the stable synthesis of indole under high temperature conditions and the renewability of catalysts is achieved, and industrial applications are improved. Economical and practical.
Patent Information
- Application Number
- CN202411676403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-22
AI Technical Summary
During the synthesis of indole, the activity and stability of the copper-based catalyst is poor, resulting in a short service life and affecting industrial applications.
The copper-aluminum catalyst prepared by oxides formed by Cu, Al and additive metals. The additive metals are divalent and trivalent metals. The molar ratio of Cu to divalent additive metals is 3:1~1:3. Al The molar ratio to the trivalent additive metal is 1:3~3:1, Cu accounts for more than 60% of the total substance, and Al accounts for more than 80%. It is prepared by ball milling and calcining, and regenerated by in-situ aeration roasting.
It improves the high temperature stability and catalytic activity of copper-aluminum catalysts, extends the retention time of indole yield, and the catalyst can be regenerated multiple times to restore its initial activity, with good industrial application prospects.
Smart Images

Figure CN119175100A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthesizing indole, and in particular to a copper-aluminum catalyst, a preparation method, an application and a regeneration method thereof. Background Art
[0002] Indole is an important heterocyclic fine chemical raw material, widely used in medicine, pesticides, spices, food, feed additives, dyes and other fields. The amine method is a method for synthesizing indole in the vapor phase using aniline and ethylene glycol as reaction raw materials under the action of a metal catalyst. This method not only has low raw material prices and low production costs, but also has a simple operation process and does not generate inorganic salts and other wastes that are harmful to the environment during the reaction. It has obvious advantages and is the most economical of many indole synthesis methods. In the process of indole synthesis, the use of catalysts is particularly important.
[0003] At present, the research and development of catalysts for the process of synthesizing indole by alcoholamine has eliminated the use of highly polluting catalysts such as Pb and Cd; there is relatively little research on precious metal and rare metal catalysts; among non-precious metal catalysts, copper-based catalysts have been widely studied due to their high activity and low price. Usually, the copper-based catalysts used in the synthesis of indole by alcoholamine mainly use SiO2 as a carrier, but the overall service life of the copper-based catalyst is not long. The reason is that the aromatic byproducts N-ethylaniline and N-acetylaniline generated in the reaction are adsorbed on the catalyst surface, resulting in catalyst poisoning and deactivation. Further to the catalyst poisoning and deactivation, the existing improvement method is to introduce H2 and water vapor into the system to minimize byproducts and purge and remove byproducts. This method has a certain effect on improving the service life of the catalyst, but since the service life extended by this method is relatively limited, its industrial applicability needs to be further improved.
[0004] Therefore, in the technical field of indole synthesis, the poor catalytic activity and stability of copper-based catalysts used to synthesize indole have become technical problems that need to be solved urgently. Summary of the invention
[0005] To solve the above problems, in the first aspect, the present invention provides a copper-aluminum catalyst, wherein the copper-aluminum catalyst is an oxide formed by Cu, Al and an auxiliary metal; the auxiliary metal is a divalent auxiliary metal and / or a trivalent auxiliary metal; the divalent auxiliary metal is one or more of Mg, Zn, Ni, Ca, and Co, and the trivalent auxiliary metal is one or more of Cr, Y, La, and Fe; Among them, the ratio of the total molar number of the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Cu accounts for more than 60% of the total amount of the Cu and the divalent auxiliary metal, and the Al accounts for more than 80% of the total amount of the Al and the trivalent auxiliary metal.
[0006] Preferably, the copper-aluminum catalyst further comprises Mg; The ratio of the total molar number of the Mg, the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Mg accounts for more than 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal.
[0007] Preferably, the auxiliary metal is a divalent auxiliary metal and a trivalent auxiliary metal, the divalent auxiliary metal is Ca, and the trivalent auxiliary metal is Y; The total molar ratio of the Mg, the Cu, the divalent auxiliary metal and the Al, the trivalent auxiliary metal is 1:2; the Cu accounts for 60% of the total amount of the Mg, the Cu and the divalent auxiliary metal, the Mg accounts for 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal, and the Al accounts for 90% of the total amount of the Al and the trivalent auxiliary metal.
[0008] In a second aspect, the present invention provides a method for preparing the copper-aluminum catalyst described in the first aspect, wherein the copper-aluminum catalyst is used to synthesize indole, and the preparation method comprises: S1, after the Cu source, Al source and auxiliary metal source are uniformly mixed, they are placed in a ball mill for ball milling, and then dried to obtain a catalyst precursor; the auxiliary metal source is a divalent auxiliary metal source and / or a trivalent auxiliary metal source; the divalent auxiliary metal source is one or more of Mg, Zn, Ni, Ca, and Co sources, and the trivalent auxiliary metal source is one or more of Cr, Y, La, and Fe sources; S2, grinding the catalyst precursor and placing it in air or oxygen atmosphere, and calcining it at 800°C to 1200°C for 1 h to 6 h to obtain a copper-aluminum catalyst.
[0009] Preferably, the Cu source, Al source and auxiliary metal source are mixed uniformly, including: The Cu source, the Al source and the auxiliary metal source are uniformly mixed in a solvent; the solvent is a mixture including polyethylene glycol.
[0010] Preferably, the Cu source is one or more of copper oxide, copper hydroxide, and copper acetate, and the Al source is one or more of aluminum oxide, aluminum hydroxide, and pseudo-boehmite; The solvent is a mixture of polyethylene glycol and deionized water in a mass ratio of 0.1 to 6:100.
[0011] Preferably, the ball milling process is: adding zirconium balls with a diameter of 5 mm to 10 mm, and ball milling for 2 h to 15 h at a rotation speed of 200 r / min to 800 r / min; The drying process parameters are: drying at a temperature of 80°C to 150°C for 5 h to 24 h.
[0012] Preferably, in the process of uniformly mixing the Cu source, the Al source and the auxiliary metal source, a Mg source is mixed at the same time; wherein the Mg source is one or more of magnesium oxide, magnesium hydroxide and magnesium acetate.
[0013] In a third aspect, the present invention provides an application of a copper-aluminum catalyst, wherein the copper-aluminum catalyst described in the first aspect is used in a one-step synthesis of an indole compound or an indole derivative by an alcoholamine method.
[0014] Preferably, the application includes: Aniline and ethylene glycol are directly reacted using the copper-aluminum catalyst under the condition of hydrogen introduction, reaction temperature of 260°C to 350°C, and space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.
[0015] When the raw materials are N-methylaniline and ethylene glycol, N-methylindole can be obtained by directly using the copper-aluminum catalyst and process conditions; when the raw materials are N-ethylaniline and ethylene glycol, N-ethylindole can be obtained by directly using the copper-aluminum catalyst and process conditions; when the raw materials are m-methylaniline and ethylene glycol, 4-methylindole and 6-methylindole can be obtained by directly using the copper-aluminum catalyst and process conditions; when the raw materials are p-methylaniline and ethylene glycol, 5-methylindole can be obtained by directly using the copper-aluminum catalyst and process conditions; when the raw materials are aniline and propylene glycol, 3-methylindole can be obtained by directly using the copper-aluminum catalyst and process conditions; when the raw materials are aniline and 1,2-propylene glycol, 2-methylindole can be obtained by directly using the copper-aluminum catalyst and process conditions.
[0016] Preferably, when the raw materials are aniline and propylene glycol, the molar ratio of aniline to ethylene glycol is 9:1, and the copper-aluminum catalyst is directly used to introduce hydrogen, the reaction temperature is 260°C, and the space velocity is 3.0 h -1 The reaction was carried out under the conditions of , and 3-methylindole was obtained with a yield of 76.4% (based on glycerol).
[0017] In a fourth aspect, the present invention provides a method for regenerating a copper-aluminum catalyst, wherein the copper-aluminum catalyst after application of the third aspect is regenerated by in-situ ventilation roasting.
[0018] Preferably, the regeneration process of the copper-aluminum catalyst is as follows; Air or nitrogen containing oxygen was introduced into the reactor at a gas space velocity of 50 h -1 ~1000 h -1 Under the conditions of , the copper-aluminum catalyst after the reaction is heated and kept in situ at a heating rate of 0.1°C / min~0.5°C / min to 200°C~400°C, and kept for 15 h~20 h to obtain a regenerated copper-aluminum catalyst, and the regenerated copper-aluminum catalyst is reused in the reaction of synthesizing indole compounds or indole derivatives.
[0019] Compared with the prior art, the present invention has the following advantages: The present invention provides a copper-aluminum catalyst, a preparation method, an application and a regeneration method thereof, and relates to the technical field of synthesizing indole. The copper-aluminum catalyst is an oxide formed by Cu, Al and an auxiliary metal; the auxiliary metal is a divalent auxiliary metal and / or a trivalent auxiliary metal; wherein the total molar number of Cu and the divalent auxiliary metal and the total molar number of Al and the trivalent auxiliary metal are in a ratio of 3:1 to 1:3, Cu accounts for more than 60% of the total amount of Cu and the divalent auxiliary metal, and Al accounts for more than 80% of the total amount of Al and the trivalent auxiliary metal. The copper-aluminum catalyst provided by the embodiment of the present invention has high stability and catalytic activity for synthesizing indole under high temperature conditions, the indole yield can be maintained at more than 50% when the reaction is 200 hours, and the copper-aluminum catalyst can be basically restored to the initial activity after being regenerated by multiple in-situ roasting, has good economy and practicality, and has good industrial application prospects.
[0020] The copper-aluminum catalyst provided in the embodiment of the present invention improves stability and catalytic activity through the following two aspects: on the one hand, by introducing auxiliary metals, the spatial structure of the copper-aluminum catalyst is changed, the release rate of copper when the copper-aluminum catalyst is used is controlled, and the deactivation caused by agglomeration and sintering of the released copper is slowed down, thereby improving the stability and catalytic activity of the copper-aluminum catalyst; on the other hand, since the copper-aluminum catalyst does not introduce a carrier and thus has no complex pore structure, its specific surface area is relatively small, and the adsorption effect on aromatic by-products is small, which reduces the poisoning deactivation of the catalyst to a certain extent, thereby improving the stability and catalytic activity of the copper-aluminum catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A flow chart of a method for preparing a copper-aluminum catalyst provided in an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of the copper-magnesium-aluminum catalyst provided in Example 4 of the present invention; Figure 3 This is the pore size distribution diagram of the copper-magnesium-aluminum catalyst provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0023] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0024] Specific experimental steps or conditions are not specified in the embodiments, and the operations or conditions of the conventional experimental steps described in the prior art in the art can be carried out. The reagents used and other instruments that do not specify the manufacturer are all conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0025] In a first aspect, the present invention provides a copper-aluminum catalyst, wherein the copper-aluminum catalyst is an oxide formed by Cu, Al and a promoter metal; the promoter metal is a divalent promoter metal and / or a trivalent promoter metal; the divalent promoter metal is one or more of Mg, Zn, Ni, Ca, and Co, and the trivalent promoter metal is one or more of Cr, Y, La, and Fe; Among them, the ratio of the total molar number of the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Cu accounts for more than 60% of the total amount of the Cu and the divalent auxiliary metal, and the Al accounts for more than 80% of the total amount of the Al and the trivalent auxiliary metal.
[0026] The specific surface area of the copper-aluminum catalyst is 90 m 2 / g~120 m 2 / g; The copper-aluminum catalyst provided in the embodiment of the present invention improves stability and catalytic activity in the following two aspects: on the one hand, the spatial structure of the copper-aluminum catalyst is changed by introducing an auxiliary metal, the release rate of copper in the copper-aluminum catalyst is controlled when it is used, and the deactivation caused by the agglomeration and sintering of the released copper is slowed down, thereby improving the stability and catalytic activity of the copper-aluminum catalyst; on the other hand, since the copper-aluminum catalyst does not introduce a carrier, it has no complex pore structure, its specific surface area is relatively small, and the adsorption effect on aromatic by-products is small, which reduces the poisoning and deactivation of the catalyst to a certain extent, thereby improving the stability and catalytic activity of the copper-aluminum catalyst. The copper-aluminum catalyst provided in the embodiment of the present invention has high stability and catalytic activity for synthesizing indole under high temperature conditions (300 ° C), and the indole yield can be maintained at more than 50% when reacting for 200 h under high temperature conditions (300 ° C), and has good industrial application prospects.
[0027] In this embodiment, Cu and Al in the copper-aluminum catalyst form a certain structure at a certain ratio (the total molar ratio of Cu to Al is 3:1~1:3); the divalent auxiliary metal replaces part of the Cu in the certain structure, regulates the spatial structure of the copper-aluminum catalyst, thereby controlling the release rate of copper when the copper-aluminum catalyst is in use, slowing down the deactivation caused by agglomeration and sintering of the released copper, thereby improving the catalytic activity of the copper-aluminum catalyst; the trivalent auxiliary metal replaces part of the Al in the certain structure, regulates the spatial structure of the copper-aluminum catalyst, thereby controlling the release rate of copper when the copper-aluminum catalyst is in use, slowing down the deactivation caused by agglomeration and sintering of the released copper, thereby improving the catalytic activity of the copper-aluminum catalyst; after the replacement, Cu accounts for more than 60% of the total amount of Cu and the divalent auxiliary metal, and after the replacement, Al accounts for more than 80% of the total amount of Al and the trivalent auxiliary metal.
[0028] In some embodiments of the present invention, the copper-aluminum catalyst further comprises Mg; The ratio of the total molar number of the Mg, the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Mg accounts for more than 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal.
[0029] In this embodiment, on the basis of the replacement of divalent auxiliary metal and / or trivalent auxiliary metal, Mg also replaces part of Cu in a certain structure, further regulating the spatial structure of the copper-aluminum catalyst, thereby controlling the release rate of copper when the copper-aluminum catalyst is used, and slowing down the deactivation caused by the agglomeration and sintering of the released copper. On the other hand, since part of Mg enters the structure, the distribution of cations in the structure is changed, so that the surface properties of the catalyst change, which is more conducive to the reaction. Thereby further improving the stability and catalytic activity of the copper-aluminum catalyst.
[0030] In some embodiments of the present invention, the auxiliary metal is a divalent auxiliary metal and a trivalent auxiliary metal, the divalent auxiliary metal is Ca, and the trivalent auxiliary metal is Y; The total molar ratio of the Mg, the Cu, the divalent auxiliary metal and the Al, the trivalent auxiliary metal is 1:2; the Cu accounts for 60% of the total amount of the Mg, the Cu and the divalent auxiliary metal, the Mg accounts for 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal, and the Al accounts for 90% of the total amount of the Al and the trivalent auxiliary metal.
[0031] The copper-aluminum catalyst provided in this example has the highest stability and catalytic activity for synthesizing indole under high temperature conditions, and the indole yield can be maintained at 60.7% when the reaction is continued for 200 h.
[0032] In a second aspect, the present invention provides a method for preparing the copper-aluminum catalyst described in the first aspect, wherein the copper-aluminum catalyst is used to synthesize indole, and the preparation method comprises: S1, after the Cu source, Al source and auxiliary metal source are uniformly mixed, they are placed in a ball mill for ball milling, and then dried to obtain a catalyst precursor; the auxiliary metal source is a divalent auxiliary metal source and / or a trivalent auxiliary metal source; the divalent auxiliary metal source is one or more of Mg, Zn, Ni, Ca, and Co sources, and the trivalent auxiliary metal source is one or more of Cr, Y, La, and Fe sources; S2, grinding the catalyst precursor and placing it in air or oxygen atmosphere, and calcining it at 800°C to 1200°C for 1 h to 6 h to obtain a copper-aluminum catalyst.
[0033] Specifically, the divalent auxiliary metal source is one or more of the oxides, hydroxides, and acetates of Mg, Zn, Ni, Ca, and Co, and the trivalent auxiliary metal source is one or more of the oxides, hydroxides, and acetates of Cr, Y, La, and Fe.
[0034] In the embodiment of the present invention, a catalyst precursor is first obtained by solid-liquid ball milling, and the obtained catalyst precursor is calcined at a high temperature to cause an oxidation reaction to obtain an oxide formed by Cu, Al and the auxiliary metal.
[0035] The preparation method provided by the present invention is simple, easy to operate, low in cost, and does not generate three waste substances in the entire preparation process, which is green and environmentally friendly. Specifically, since no nitrate is used as a Cu source, an Al source or an auxiliary metal source, no waste gas and waste liquid are generated in the entire preparation process, which is green and environmentally friendly.
[0036] In some embodiments of the present invention, the Cu source, the Al source and the auxiliary metal source are uniformly mixed, including: The Cu source, the Al source and the auxiliary metal source are uniformly mixed in a solvent; the solvent is a mixture including polyethylene glycol.
[0037] In some embodiments of the present invention, the Cu source is one or more of copper oxide, copper hydroxide, and copper acetate, the Al source is one or more of aluminum oxide, aluminum hydroxide, and pseudo-boehmite; and the solvent is a mixture of polyethylene glycol and deionized water in a mass ratio of 0.1 to 6:100.
[0038] In this embodiment, since neither the Cu source nor the Al source uses nitrate, no waste gas is generated during the entire preparation process, which is green and environmentally friendly; if the Cu source, Al source or auxiliary metal source uses nitrate, toxic gases such as nitric oxide and nitrogen dioxide will be generated.
[0039] The preparation process of the solvent in this embodiment is: adding 0.1% to 6% of polyethylene glycol by mass of deionized water to deionized water and heating until it is completely dissolved, and the obtained mixture of deionized water and polyethylene glycol is used as the solvent; wherein the polyethylene glycol is a mixture of one or more of PEG-600, PEG-800, PEG-1000, and PEG-1500.
[0040] In the prior art, when preparing the catalyst, the solvent usually used in ball milling is a mixture of water and ethanol. In this embodiment, polyethylene glycol is added to make the various solid compounds more evenly dispersed, thereby improving the performance of the catalyst to a certain extent; the various solid compounds refer to the Cu source, the Al source and the auxiliary metal source. In addition, since ethanol is not used as a solvent in this embodiment, no waste liquid is generated during the entire preparation process, which has the characteristics of being green and pollution-free.
[0041] In some embodiments of the present invention, the ball milling process is: adding zirconium balls with a diameter of 5 mm to 10 mm, and ball milling for 2 h to 15 h at a rotation speed of 200 r / min to 800 r / min; The drying process parameters are: drying at a temperature of 80°C to 150°C for 5 h to 24 h.
[0042] In some embodiments of the present invention, during the process of uniformly mixing the Cu source, the Al source and the auxiliary metal source, a Mg source is also mixed; wherein the Mg source is one or more of magnesium oxide, magnesium hydroxide and magnesium acetate.
[0043] In this embodiment, on the basis of the replacement of divalent auxiliary metals and / or trivalent auxiliary metals, Mg also replaces part of Cu in a certain structure, thereby further regulating the spatial structure of the copper-aluminum catalyst and controlling the release rate of copper when the copper-aluminum catalyst is in use, slowing down the deactivation caused by agglomeration and sintering of the released copper, thereby further improving the catalytic activity of the copper-aluminum catalyst.
[0044] In a third aspect, the present invention provides an application of a copper-aluminum catalyst, wherein the copper-aluminum catalyst described in the first aspect is used in a one-step synthesis of an indole compound or an indole derivative by an alcoholamine method.
[0045] The principle of synthesizing indole based on the alcoholamine method is different from the principle of synthesizing indole by other methods. Therefore, the copper-aluminum catalyst provided by the present invention is only used for synthesizing indole from aniline and ethylene glycol. The copper-aluminum catalyst is used for the synthesis of indole compounds and can also be used for the preparation of indole derivatives.
[0046] The copper-aluminum catalyst provided in the embodiment of the present invention has high stability and catalytic activity for synthesizing indole under high temperature conditions. The indole yield can be maintained at more than 50% when the reaction is continued for 200 h, and has good industrial application prospects.
[0047] In some embodiments of the present invention, the application includes: Aniline and ethylene glycol are directly reacted using the copper-aluminum catalyst under the condition of continuous introduction of hydrogen, reaction temperature of 260°C to 350°C, and space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:1.
[0048] In the prior art, the prepared catalyst is usually pre-reduced by introducing hydrogen before being used as a catalyst for synthesizing indole by the alcoholamine process, so as to release all the active copper of the catalyst, so that during the reaction of aniline and ethylene glycol, the active copper can well promote the reaction. However, when all the active copper is released, copper agglomeration and sintering are likely to occur, resulting in a rapid deactivation of the catalytic activity.
[0049] The copper-aluminum catalyst obtained by the present invention does not need to be pre-reduced before use, which simplifies the application steps on the one hand, and on the other hand, since the present invention improves the stability of the copper-aluminum catalyst, the present embodiment can avoid agglomeration and sintering of active copper during the synthesis of indole. Furthermore, the active copper that has not agglomerated and sintered improves the catalytic activity of the copper-aluminum catalyst to a certain extent.
[0050] Specifically, the copper-aluminum catalyst obtained by the preparation method provided by the present invention exists in a stable structure; because auxiliary metals and magnesium are added to the copper-aluminum catalyst, the stability of the copper-aluminum catalyst is improved, and further, during the gas phase reaction of aniline and ethylene glycol, copper in the stable structure in the form of copper oxide is slowly released and reduced to active copper while reacting in a hydrogen atmosphere. The addition of auxiliary metals and magnesium controls the release rate of copper to a certain extent, slows down the deactivation caused by agglomeration and sintering of the released copper, and thus improves the catalytic activity of the copper-aluminum catalyst.
[0051] In a fourth aspect, the present invention provides a method for regenerating a copper-aluminum catalyst, wherein the copper-aluminum catalyst after application of the third aspect is regenerated by in-situ ventilation roasting.
[0052] The copper-aluminum catalyst provided in an embodiment of the present invention is regenerable. The copper-aluminum catalyst is used in the reaction of synthesizing indole compounds or indole derivatives. After the reaction is completed, the reacted and inactive copper-aluminum catalyst is regenerated through a simple roasting method. The catalytic performance of the regenerated copper-aluminum catalyst is equivalent to that of the newly prepared copper-aluminum catalyst.
[0053] In some embodiments of the present invention, the regeneration process of the copper-aluminum catalyst is as follows; Air or nitrogen containing oxygen is introduced into the reactor at a gas space velocity of 50 h -1 ~1000h -1 Under the conditions of , the copper-aluminum catalyst after the reaction is heated and kept in situ at a heating rate of 0.1°C / min~0.5°C / min to 200°C~400°C, and kept for 15 h~20 h to obtain a regenerated copper-aluminum catalyst, and the regenerated copper-aluminum catalyst is reused in the reaction of synthesizing indole compounds or indole derivatives.
[0054] In order to enable those skilled in the art to better understand the present invention, the preparation method provided by the present invention is described below through multiple specific examples.
[0055] Comparative Example 1 9.76 g of copper hydroxide [Cu(OH)2] and 15.6 g of aluminum hydroxide [Al(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed and added to the above mixture, and the mixture was stirred and mixed evenly, and then placed in a ball mill, and then 200 mL of zirconium balls with a diameter of 10 mm were added, and ball milling was performed at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100 °C for 16 h to obtain a catalyst precursor.
[0056] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a catalyst with a specific surface area of 101.2556 m 2 / g.
[0057] Application of catalyst: 1.5 g of the obtained catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0058] Comparative Example 2 5.86 g of copper hydroxide [Cu(OH)2], 2.33 g of magnesium hydroxide [Mg(OH)2] and 15.6 g of aluminum hydroxide [Al(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed and added to the above mixture, and the mixture was stirred and mixed evenly, and then placed in a ball mill, and then 200 mL of zirconium balls with a diameter of 10 mm were added, and ball milling was carried out at a rotation speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0059] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a catalyst with a specific surface area of 102.1229 m 2 / g.
[0060] Application of catalyst: 1.5 g of the obtained catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0061] Example 1 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.99 g of zinc hydroxide [Zn(OH)2] and 15.6 g of aluminum hydroxide [Al(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-600 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0062] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere and calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 99.0622 m 2 / g.
[0063] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0064] Example 2 5.86 g of copper hydroxide [Cu(OH)2], 2.33 g of magnesium hydroxide [Mg(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 3.8 g of lanthanum hydroxide [La(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-600 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0065] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 103.6954 m 2 / g.
[0066] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0067] Example 3 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3], and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-600 was added and heated to 80 °C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, placed in a ball mill, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100 °C for 16 h. The catalyst precursor was obtained.
[0068] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 105.2349 m 2 / g.
[0069] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0070] Example 4 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-800 was added and heated to 80°C to dissolve it completely, and then added to the above mixture and stirred and mixed evenly, and then placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0071] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 96.8756 m 2 / g.
[0072] like Figure 2 The scanning electron microscope image of the copper-magnesium-aluminum catalyst of this embodiment is shown. Figure 3 Shown is the pore size distribution diagram of the copper-magnesium-aluminum catalyst of this example.
[0073] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0074] Example 5 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 4.8 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture and stirred and mixed evenly, and then placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0075] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 99.0266 m 2 / g.
[0076] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0077] Example 6 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1500 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0078] The catalyst precursor was transferred to a muffle furnace and heated to 800 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 1 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 100.2365 m 2 / g.
[0079] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0080] Example 7 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0081] The catalyst precursor was transferred to a muffle furnace and heated to 1200 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 6 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 102.3634 m 2 / g.
[0082] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0083] Example 8 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.93 g of cobalt hydroxide [Co(OH)2], 18.72 g of aluminum hydroxide [Al(OH)3] and 6.18 g of chromium hydroxide [Cr(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0084] The catalyst precursor was transferred to a muffle furnace and heated to 1200 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 6 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 108.3658 m 2 / g.
[0085] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0086] Example 9 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.93 g of cobalt hydroxide [Co(OH)2], 6.24 g of aluminum hydroxide [Al(OH)3] and 2.06 g of chromium hydroxide [Cr(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture and stirred and mixed evenly, and then placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0087] The catalyst precursor was transferred to a muffle furnace and heated to 1200 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 6 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 99.6237 m 2 / g.
[0088] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h-1 The evaluation conditions and results are shown in Table 1.
[0089] Example 10 17.57 g of copper hydroxide [Cu(OH)2], 5.25 g of magnesium hydroxide [Mg(OH)2], 2.79 g of cobalt hydroxide [Co(OH)2], 6.24 g of aluminum hydroxide [Al(OH)3] and 2.06 g of chromium hydroxide [Cr(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture, stirred and mixed evenly, and placed in a ball mill jar, and then 200 ml of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0090] The catalyst precursor was transferred to a muffle furnace and heated to 1200 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 6 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 102.2658 m 2 / g.
[0091] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 300 °C, and the feed reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0092] Table 1 Evaluation conditions and results of examples and comparative examples
[0093] Embodiment 11 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture and stirred and mixed evenly, and then placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0094] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere and calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 99.8957 m 2 / g.
[0095] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 280 °C, and the feeding reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0096] Example 12 5.86 g of copper hydroxide [Cu(OH)2], 1.75 g of magnesium hydroxide [Mg(OH)2], 0.74 g of calcium hydroxide [Ca(OH)2], 14.04 g of aluminum hydroxide [Al(OH)3] and 2.8 g of yttrium hydroxide [Y(OH)3] were mixed and stirred to obtain a mixture; 80 mL of deionized water was weighed, 2.4 g of polyethylene glycol PEG-1000 was added and heated to 80°C to dissolve it completely, and then added to the above mixture and stirred and mixed evenly, and then placed in a ball mill jar, and then 200 mL of 10 mm diameter zirconium balls were added, and ball milled at a speed of 300 r / min for 2 h; the ball-milled sample was dried at 100°C for 16 h to obtain a catalyst precursor.
[0097] The catalyst precursor was transferred to a muffle furnace and heated to 1000 °C at a heating rate of 5 °C / min in an air atmosphere. The catalyst was calcined for 3 h to obtain a copper-magnesium-aluminum catalyst with a specific surface area of 109.1894 m 2 / g.
[0098] Application of copper-magnesium-aluminum catalyst: 1.5 g of the obtained copper-magnesium-aluminum catalyst was loaded into the reactor, the temperature was raised to 350 °C, and the feeding reaction was started. The molar ratio of ethylene glycol to aniline was 1:7, and the space velocity was 0.5 h -1 The evaluation conditions and results are shown in Table 1.
[0099] Example 13 Based on the copper-magnesium-aluminum catalyst prepared in Example 4, the catalyst deactivation and regeneration method is described. When the activity of the copper-magnesium-aluminum catalyst in the indole synthesis application process is reduced to a reaction yield of less than 40%, the copper-magnesium-aluminum catalyst is in situ deactivated and regenerated. The regeneration process is as follows: air is introduced into the reactor at a space velocity of 100 h -1 , the temperature was raised to 300 ℃ at a heating rate of 0.15 ℃ / min and kept at this temperature for 20 h, and the regeneration was completed.
[0100] The regenerated copper-magnesium-aluminum catalyst was further used in the indole synthesis reaction of ethylene glycol and aniline according to the copper-magnesium-aluminum catalyst application process shown in Example 4.
[0101] After in-situ regeneration, the reaction effects of the regenerated catalysts were compared and tested and recorded. The specific results are as follows: after regeneration once, the indole yield in the test for 200 h was 59.1%; after regeneration twice, the indole yield in the test for 200 h was 58.6%.
[0102] Embodiment 14 In this embodiment, when the temperature is increased by 2 °C / min compared with Example 13, after regeneration once, the indole yield in the test for 200 h is 32.7%; in the same way, after the second regeneration, the indole yield in the test for 200 h is 21.5%. This is because in order to ensure that the catalyst still has a high indole synthesis yield after regeneration, it is necessary to ensure that the carbon deposits attached to the used catalyst can be fully removed without destroying the original microstructure of the catalyst, and it is necessary to ensure that the temperature is slowly increased to fully remove the residues in each tiny hole of the catalyst.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0104] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0105] The above is a detailed introduction to a copper-aluminum catalyst, preparation method, application and regeneration method provided by the present invention. Specific examples are used in this article to illustrate the principle and implementation method of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technicians in this field, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A copper-aluminum catalyst, characterized in that The copper-aluminum catalyst is an oxide formed by Cu, Al and an auxiliary metal; the auxiliary metal is a divalent auxiliary metal and / or a trivalent auxiliary metal; the divalent auxiliary metal is one or more of Mg, Zn, Ni, Ca, and Co, and the trivalent auxiliary metal is one or more of Cr, Y, La, and Fe; Among them, the ratio of the total molar number of the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Cu accounts for more than 60% of the total amount of the Cu and the divalent auxiliary metal, and the Al accounts for more than 80% of the total amount of the Al and the trivalent auxiliary metal.
2. The copper-aluminum catalyst according to claim 1, characterized in that The copper-aluminum catalyst also includes Mg; The ratio of the total molar number of the Mg, the Cu and the divalent auxiliary metal to the total molar number of the Al and the trivalent auxiliary metal is 3:1~1:3; the Mg accounts for more than 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal.
3. The copper-aluminum catalyst according to claim 2, characterized in that The auxiliary metal is a divalent auxiliary metal and a trivalent auxiliary metal, the divalent auxiliary metal is Ca, and the trivalent auxiliary metal is Y; The total molar ratio of the Mg, the Cu, the divalent auxiliary metal and the Al, the trivalent auxiliary metal is 1:2; the Cu accounts for 60% of the total amount of the Mg, the Cu and the divalent auxiliary metal, the Mg accounts for 30% of the total amount of the Mg, the Cu and the divalent auxiliary metal, and the Al accounts for 90% of the total amount of the Al and the trivalent auxiliary metal.
4. A method for preparing the copper-aluminum catalyst according to any one of claims 1 to 3, characterized in that: The copper-aluminum catalyst is used to synthesize indole, and the preparation method comprises: S1, after the Cu source, Al source and auxiliary metal source are uniformly mixed, they are placed in a ball mill for ball milling, and then dried to obtain a catalyst precursor; the auxiliary metal source is a divalent auxiliary metal source and / or a trivalent auxiliary metal source; the divalent auxiliary metal source is one or more of Mg, Zn, Ni, Ca, and Co sources, and the trivalent auxiliary metal source is one or more of Cr, Y, La, and Fe sources; S2, grinding the catalyst precursor and placing it in air or oxygen atmosphere, and calcining it at 800°C to 1200°C for 1 h to 6 h to obtain a copper-aluminum catalyst.
5. The method for preparing the copper-aluminum catalyst according to claim 4, characterized in that: The Cu source, Al source and auxiliary metal source are mixed evenly, including: The Cu source, the Al source and the auxiliary metal source are uniformly mixed in a solvent; the solvent is a mixture including polyethylene glycol.
6. The method for preparing the copper-aluminum catalyst according to claim 5, characterized in that: The Cu source is one or more of copper oxide, copper hydroxide, and copper acetate, and the Al source is one or more of aluminum oxide, aluminum hydroxide, and pseudo-boehmite; The solvent is a mixture of polyethylene glycol and deionized water in a mass ratio of 0.1 to 6:
100.
7. The method for preparing a copper-aluminum catalyst according to claim 4, characterized in that: The ball milling process is as follows: adding zirconium balls with a diameter of 5 mm to 10 mm, and ball milling for 2 h to 15 h at a rotation speed of 200 r / min to 800 r / min; The drying process parameters are: drying at a temperature of 80°C to 150°C for 5 h to 24 h.
8. The method for preparing a copper-aluminum catalyst according to claim 4, characterized in that: In the process of uniformly mixing the Cu source, the Al source and the auxiliary metal source, a Mg source is mixed at the same time; wherein the Mg source is one or more of magnesium oxide, magnesium hydroxide and magnesium acetate.
9. An application of a copper-aluminum catalyst, characterized in that: The copper-aluminum catalyst described in any one of claims 1 to 3 is used in the one-step synthesis of indole compounds or indole derivatives by the alcoholamine method.
10. The use of the copper-aluminum catalyst according to claim 9, characterized in that: The applications include: Aniline and ethylene glycol are directly reacted using the copper-aluminum catalyst under the condition of hydrogen introduction, reaction temperature of 260°C to 350°C, and space velocity of 0.1 h -1 ~3.0 h -1 to obtain an indole compound or an indole derivative; wherein the molar ratio of aniline to ethylene glycol is 1:1 to 9:
1.
11. A method for regenerating a copper-aluminum catalyst, characterized in that: The copper-aluminum catalyst after application of any of the above claims 9-10 is regenerated by in-situ ventilation calcination.
12. The method for regenerating a copper-aluminum catalyst according to claim 11, characterized in that: The regeneration process of the copper-aluminum catalyst is as follows: Air or nitrogen containing oxygen was introduced into the reactor at a gas space velocity of 50 h -1 ~1000 500 h -1 Under the conditions of , the copper-aluminum catalyst after the reaction is heated and kept in situ at a heating rate of 0.1°C / min~0.5°C / min to 200°C~400°C, and kept for 2 h~20 h to obtain a regenerated copper-aluminum catalyst, which is reused in the reaction of synthesizing indole compounds or indole derivatives.
Citation Information
Patent Citations
Ethylene glycol catalyst prepared by dimethyl oxalate plus hydrogen and preparation method and application thereof
CN101444735A
Catalyst for preparing 1,4-butanediol or tetrahydrofuran from selective hydrogenation of dimethyl maleate and preparation method thereof
CN101502803A
Method for preparing and synthetizing methanol catalyst from copper-based waste methanol catalyst recovered solution
CN103480379A
Method for synthesizing indole compound by double-effect catalysis of hydrotalcite catalyst
CN106179294A
Copper-based catalyst for methanol to hydrogen as well as preparation method and application thereof
CN108745363A
